JSS2: MATHEMATICS - 2ND TERM
-
Transactions in the Homes and Offices | Week 18 Topics|1 Quiz
-
Expansion and Factorization of Algebraic Expressions | Week 24 Topics|1 Quiz
-
Algebraic Expansion and Factorization of Algebraic Expression | Week 34 Topics|1 Quiz
-
Algebraic Fractions I | Week 44 Topics|1 Quiz
-
Addition and Subtraction of Algebraic Fractions | Week 52 Topics|1 Quiz
-
Solving Simple Equations | Week 64 Topics|1 Quiz
-
Linear Inequalities I | Week 74 Topics|1 Quiz
-
Linear Inequalities II | Week 82 Topics|1 Quiz
-
Quadrilaterals | Week 92 Topics|1 Quiz
-
Angles in a Polygon | Week 104 Topics|1 Quiz
-
The Cartesian Plane Co-ordinate System I | Week 113 Topics|1 Quiz
-
The Cartesian Plane Co-ordinate System II | Week 121 Topic|1 Quiz
Expanding Brackets
Topic Content:
- Expanding Brackets
In expanding brackets, the multiplications sign \(\scriptsize \times \) is usually not written. For instance;
\( \scriptsize 2(7a \: + \: 5a) \\ = \scriptsize 2 \: \times \: (7a \: + \: 5a) \)2, multiplies everything inside the brackets
∴ \( \scriptsize 2(7a \: + \: 5a) \\= \scriptsize 2 (7a) \: + \: 2(5a) \\ = \scriptsize 2 \: \times \: 7a \: + \: 2 \: \times \: 5a \\ = \scriptsize 14a \: + \: 10a \\ = \scriptsize 24a \)
Example 2.4.1:
Remove the brackets and simplify the following expressions;
a. 5(x + y)
b. -2 (p – q – r)
c. 10x – 2(2x + 7y)
d. 2(3x – 4) – 3(5 – 2x)
e. 5(2x – 1) + 4(x – 3)
Solution
a. 5(x + y)
= 5 (x) + 5(y)
= \( \scriptsize 5 \: \times \: x \: + \: 5 \: \times \: y \\ \scriptsize = 5x \: + \: 5y\)
b. -2 (p – q – r)
= -2(p) -2 (-q) -2 (-r)
= -2(p) -2 (-q) -2 (-r)
= -2 × p + 2 × q + 2 × r
= -2p + 2q + 2r
c. 10x – 2 (2x + 7y)
= 10x – 2(2x) – 2(+7y)
= \( \scriptsize 10x \: – \: 2 \: \times \: 2x \: – \: 2 \: \times \: 7y \)
= \( \scriptsize 10x \: – \: 4x \: – \:14y \)
= \( \scriptsize 6x \: – \: 14y \)
d. 2(3x – 4) – 3(5 – 2x)
= 2(3x) + 2(-4) – 3(5) – 3(-2x)
= \( \scriptsize 2 \: \times \: 3x \: + \: 2 \: \times \: – \: 4 \: -\: 3 \: \times \: 5 \: – \: 3 \: \times \: -2x \)
= \( \scriptsize 6x \: – \: 8 \: -\: 15 \: + \: 6x \)
Collect like terms
= \( \scriptsize 6{\color{Blue} x} \: – \: 8 \: -\: 15 \: + \: 6{\color{Blue} x} \)
= \( \scriptsize 6x \: + \: 6x \: – \: 8 \: -\: 15 \)
= \( \scriptsize 12x \: – \: 23 \)
e. 5(2x – 1) + 4(x – 3)
= 5(2x) + 5(-1) + 4(x) + 4(-3)
= 10x – 5 + 4x – 12
Collect like terms
= 10x – 5 + 4x – 12
= 10x + 4x – 5 – 12
= 14x – 17
Evaluation Questions:
Remove the brackets and simplify the following expressions
1. -2(x + y)
2. -5(4a – 7b)
3. -5(8d – 5e – f)
4. 4(2b + a) + 5(b + 2a)
5. -5(4a + 8b)
6. x – 7(2x – 2)
Answer
1. -2x – 2y
2. -20a + 35b
3. -40d + 25e + 5f
4. 14a + 13b
5. -20a – 40b
6. -13x + 14